Effective management of peripheral vertigo due to benign paroxysmal positional vertigo with betahistine, in the real-world setting: an expert survey with ENT specialists in India - Juneja, Akash; Bhargava, Rajan (International Journal of Research in Medical Sciences, 2025)
Background: Benign paroxysmal positional vertigo (BPPV) commonly causes peripheral vertigo and is treated with canalith repositioning maneuvers (CRM). Yet, a subset of patients continues to experience vertigo called residual dizziness after undergoing CRM. Objective was to understand the role of betahistine 48 mg per day in prevention of recurrent vertigo and prevention of residual dizziness in patients with BPPV based on expert perceptions. Methods: Forty ear, nose and throat (ENT) specialists or otolaryngologists from diverse regions across India who were treating patients with peripheral vertigo were invited to participate in QR code facilitated survey regarding their approach to treating peripheral vertigo in the real-world setting. Results: 23 respondents (57%) reported that 10-25% of their patients had recurrence of vertigo. 24 respondents (60%) opined that both impaired vestibular compensation due to insufficient dose (less than 48 mg/day) and duration (less than 3 months) of betahistine and remnant otoliths cause recurrence of vertigo. 57% participants adopted this approach to prevent residual dizziness namely: 1) increase dose of betahistine to 48 mg/day and 2) increase the duration of use of betahistine to 3 months. 40% physicians opined that 75-90% reduction in vertigo episodes is seen with 48 mg per day of betahistine. Conclusions: Betahistine is preferred to treat peripheral vertigo due to BPPV. Betahistine is prescribed in the dose of 48 mg per day for a duration of at least 3 months post repositioning manoeuvres effectively reduces vertigo, reduces recurrence and residual dizziness by facilitating vestibular compensation and improved vestibular blood supply.